Detour Central Florida : history by the roadside - Husmann, Jennifer (The History Press, 2026)
Central Florida is more than theme parks and condos. Beneath the surface lies a rich and surprising past. River pirates once ruled its inland waterways. Spanish forts and Confederate hideouts marked its wild frontier. Tarpon Springs became home to the largest Greek-American community in the U.S. French pirates sailed through Pinellas County's bays and barrier islands. During Prohibition, the Harris Chain of Lakes tied the region to Caribbean rum-runners and Gatsby-style parties. Along the Treasure Coast, lighthouse keepers risked their lives to guide sailors past deadly shoals. Native Floridian Jennifer Husmann brings these forgotten stories to life with vivid detail and deep research. --